Klasifikasi Gangguan Jiwa Skizofrenia Menggunakan Algoritme Decision Tree C5.0 - Febriyani Riyanda; Imam Cholissodin; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Schizophrenia is one of psychiatric disorders which gets much concern all over the world. Schizophrenia requires a quick and precise treatment due to its chronic tendency. However, the insufficient service on mental disorder can cause patients are not addressed immediately and the height subjectivity amongst psychiatrists in determining the type of schizophrenia has similar symtoms can lead to schizophrenia classification errors. In this classification of mental disorders use the C5.0 decision tree algorithm, which has additional functions such as boosting. The data used were 106 data taken from the Dr. Radjiman Wediodiningrat Lawang Psychiatric Hospital, this data consists of 89 trained data and 17 test data. The test method being used is accuracy. Based on the results of testing the C5.0 parameter, the highest average accuracy value was 85.884% with the number of data = 71 samples, the number of trials or the number of decision tree = 100.